2015
DOI: 10.1055/s-0035-1563714
|View full text |Cite
|
Sign up to set email alerts
|

Tubular Injury Biomarkers to Detect Gentamicin-Induced Acute Kidney Injury in the Neonatal Intensive Care Unit

Abstract: GM administration to neonates is associated with renal damage reflected by a more pronounced increase in sCr preceded by urinary excretion of biomarkers. Urinary biomarkers may be useful for earlier identification of renal injury in neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…This finding is in accordance with other studies and may reflect an under-recognized tubular injury [19]. Jansen et al [20] describe an increased urinary excretion of different biomarkers after gentamicin administration in a neonatal population. This rise precedes the peak of serum creatinine and the decrease in urinary output.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in accordance with other studies and may reflect an under-recognized tubular injury [19]. Jansen et al [20] describe an increased urinary excretion of different biomarkers after gentamicin administration in a neonatal population. This rise precedes the peak of serum creatinine and the decrease in urinary output.…”
Section: Discussionsupporting
confidence: 91%
“…Creatinine undergoes glomerular filtration and tubular secretion to a lesser degree. Such elevated serum creatine levels can be associated with drug-induced oxidative alteration of mitochondrial or cytosolic creatine kinases, oxidative damage-prone enzymes 14 . Blood urea nitrogen is a metabolic waste product excreted in urine by the kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have evaluated the impact of AG on urinary markers of proximal tubule damage. These studies have shown that AG exposure results in the elevation of urinary biomarkers, including those that signify proximal tubular damage, irrespective of rise in serum creatinine [31**,35*,36]. These data suggest there may be damage resulting from AG exposure that is not detected by a rise in serum creatinine, which warrants further study.…”
Section: Nephrotoxic Medicationsmentioning
confidence: 99%